“The example and ornament in this transplanted Christian Colony”: The “Death Writing” of St. Catherine Tekakwitha and Pierre François Xavier de Charlevoix’s Histoire et description générale de la Nouvelle-France (1744) - Plante, Kelly (Lumen, 2023)
Interdisciplinary scholarship in the fields of Native American and Indigenous Studies (NAIS), ethnography, anthropology, and history has widely debated the powerful biography of St. Catherine Tekakwitha, the first Indigenous saint. This essay close-reads life writings by and about Tekakwitha as so death-centric that they can be referred to as “death writing.” Death writings document relationships among the living and the dead. This essay examines Indigenous materials alongside a colonial text: first Tekakwitha’s participation in the tradition of wampum, followed by Jesuit explorer and author Pierre François Xavier de Charlevoix’s obituary of her appended to his History and description of New-France (1744). This dual approach affords two perspectives on the power of Tekakwitha’s memory: both Tekakwitha and Charlevoix contributed to the emergence of modern forms of life writing in the eighteenth century. I present Charlevoix’s monumental text as an obituary on a macro level, of the dying French colonial and Jesuit order, and on a micro level, with its appended collection of obituaries of Indigenous individuals, with the foremost presented as Tekakwitha. I argue that New-France asserts the importance of France, the Jesuits, and Charlevoix himself, by aligning them with the European project of colonization and by invoking the power of deceased Indigenous individuals, especially Tekakwitha. Simultaneously, Tekakwitha’s death writing has functioned as a reservoir of power sustained by the controversy of her characterization as an exemplary Indigenous woman. The essay concludes by asserting Tekakwitha as an “active presence” who continues to shape discourse on her legacy.